The Influence of the Problem Based Learning Model on Student Learning Outcomes in the Pancasila Education Subject on the Material of My Rights and Obligations in Class III of SDN Banjar Sawah II Probolinggo - Abd Kadir Sugiharto Abd Kadir Sugiharto; Didit Yulian Kasdriyanto; Ludfi Arya Wardana (CV Edujavare Publishing, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on student learning outcomes in the Pancasila Education subject on the material of my rights and obligations in grade III of SDN Banjarsawah II Probolinggo. This study was motivated by the low learning outcomes of students, most of whom have not reached the Minimum Completion Criteria (KKM). The study used a quantitative experimental method with a pre-experimental design of one group pretest-posttest design. The population and sample of the study were all 23 grade III students of SDN Banjarsawah II Probolinggo. Data collection techniques used tests, observations, and documentation. The research instrument was in the form of 20 multiple-choice questions given in the form of a pretest and posttest. The validity test was carried out through expert judgment while the reliability test obtained a Cronbach's Alpha value of 0.676 so that the instrument was declared reliable. Data analysis was carried out using the Shapiro-Wilk normality test and the paired sample t-test. The results of the study showed that the significance value (2-tailed) was 0.000 < 0.05 and the calculated t value was 16.799 > t table of 2.025. The average pretest value of 43.47 increased to 78.69 in the posttest. Thus, it can be concluded that the Problem Based Learning (PBL) learning model has a significant effect on student learning outcomes in the Pancasila Education subject on the material of my rights and obligations in class III of SDN Banjarsawah II Probolinggo.